Growth and Cycles in Australia's Wine Industry: A Statistical Compendium, 1843 to 2013 - Anderson, Kym (University of Adelaide Press, 2015)
Another magisterial statistical compendium from Kym Anderson, with the assistance of Nanda Aryal: surely no nation's wine endeavours have ever been more precisely tracked through history than Australia's are here. The depth and intricacy of the global context, too, makes fascinating and often enlightening reading for any student of wine.